Metode Pemebelajaran PJOK Selama Masa Pandemi Covid-19 di SMP se-Kecamatan Mrebet Kabupaten Purbalingga (Indonesian Journal for Physical Education and Sport, 2022)
The problem of this research is how the Physical Education learning method during the pandemic Covid-19 in junior high schools in the Mrebet district, Purbalingga Regency. Objectives through learning methods. Descriptive qualitative research method. Data analysis uses data collection, data reduction, data presentation and drawing conclusions. The result of this study is that the method used in learning during the pandemic is online through the application platform. The results of the study concluded that the learning methods used during this pandemic period still looked poor and ineffective because of the many obstacles and obstacles from each junior high school in the Mrebet sub-district.